Vulnerable youth transits: youth guarantee as a training and labor integration policy? - Garcia-Fuentes, Juan (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The Youth Guarantee was launched after the economic crisis of 2008 to offer new employment opportunities for young people. The objective is to analyze whether the program has managed to achieve its initial proposals for labor market insertion in Granada. In the results, we consider the different possibilities of success after completion of the training received. For the discussion and conclusions, we present information from the students after completing their experience in the program, which will help us to understand whether they have managed to mitigate the adverse effects of the economic crisis and the high unemployment rates.